Gamification Impact on Human Aspects of the Organization - Meghashree Uppalike (Bina Nusantara University, 2022)
The term gamification is becoming more critical in virtual games and academia, and the economy. Gamification is described as the use of game elements in non-gaming areas such as companies. The purpose of this study is to find out how much gamification can be used in HR. The paper is divided into three parts. First, let's take a closer look at the concept of HR gamification, followed by a theoretical explanation. Later, the document describes the methodology, results, and conclusions used in the study.